2000
DOI: 10.1039/b001062f
|View full text |Cite
|
Sign up to set email alerts
|

NN bond cleavage of azobenzene through Pt/TiO2 photocatalytic reduction

Abstract: TiO 2 photocatalytic 2e 2 -reduction of azobenzene to hydrazobenzene is found to occur at l ex > 300 nm while loading of nanometer-sized Pt particles on TiO 2 induces NNN bond cleavage via 4e 2 -reduction; only photoisomerization occurs in the absence of TiO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The four-carbon intermediates we observed included fumaric acid, malic acid, tartaric acid, dihydroxyfumaric acid, and succinic acid as shown in Scheme 2. The presence of dihydroxyfumaric acid (11) was deduced in the degradations at neutral pH from reductive workups using NaBD 4 , which yield deuterated tartaric acid before silylation. The ratio of mass intensities showed that slightly more than half of the tartaric acid peak represented 11.…”
Section: Product Mixtures and Exploratory Degradationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four-carbon intermediates we observed included fumaric acid, malic acid, tartaric acid, dihydroxyfumaric acid, and succinic acid as shown in Scheme 2. The presence of dihydroxyfumaric acid (11) was deduced in the degradations at neutral pH from reductive workups using NaBD 4 , which yield deuterated tartaric acid before silylation. The ratio of mass intensities showed that slightly more than half of the tartaric acid peak represented 11.…”
Section: Product Mixtures and Exploratory Degradationsmentioning
confidence: 99%
“…Though photocatalytic degradation results in the oxidation of organic carbon to CO 2 , there are a few instances in which reductive steps (Eq. (8)) are known, such as in the reduction of azo dyes [10][11][12][13][14][15], electron poor aromatics [16][17][18], or quinones [19][20][21][22][23][24][25]. However, in many mechanistic discussions of degradations of large organic molecules, a key issue is not whether reduction of the organic occurs, but rather over the competition between processes represented in Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…4. They clearly prove that the sulphur and nitrogen heteroatoms in azo fuchsine molecule, after sonocatalytic degradation, are converted into the simple and innocuous inorganic NO 2 -, NO 3 -and SO 4 2-anions. Especially, the peak corresponding to SO 4 2-anion markedly becomes higher and higher, which represents the azo fuchsine molecule is decomposed gradually along with the ultrasonic irradiation.…”
Section: Measurement Of Sonocatalytic Degradation Activity Of the Tramentioning
confidence: 92%
“…In recent years, a great deal of effort has been devoted to develop heterogeneous catalysts with high catalytic activities for solving environmental problems [1][2][3]. The TiO 2 powder has been believed to be the most promising semiconductor material for long time, due to its superior photoreactivity, nontoxicity and long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, wastewater emissions from the textile industry contain large amounts of dyes, which are considered a major threat to the adjacent ecosystem due to their non-biodegradability, toxicity, and potential carcinogenicity [9] . Dye removal by photoinduced decomposition of pollutants on photocatalysts has been widely researched [10] .…”
Section: Introductionmentioning
confidence: 99%